Comparação do processamento sensorial e desenvolvimento motor entre lactentes pré-termo e a termo - Cabral, Thais Invenção (2012)
Preterm Infants born and/or low birth weight often spend a long period of stay in neonatal intensive care unit (NICU) because they have greater instability organic frameworks. The deployment of these units was a key milestone in the care of newborn due to reduced neonatal morbidity and mortality, especially among extremely premature and very low birth weight premature. However, admission to NICU, besides being a stressor for the infant, because too painful treatments to which is submitted, constitutes a psychosocial risk factor in development Considering the possible relation between changes in the integration of sensory information, motor development and its effects on the pre-school, proposes that the present study from the perspective of secondary prevention in Special Education. The purpose of this study is to evaluate the sensory processing and motor development of infants preterm between 4 to 6 months, compared with full-term infants. It is therefore a descriptive, cross-sectional and prospective, composed of a study group made up of premature infants (n=15) and a control group composed of full-term infants. The sample (n=30) was assessed using the Test of Sensory Functions in Infant (TSFI), and scale Alberta Infants Motor Scale (AIMS). In the preterm group, when compared motor performance with sensory processing, the result was not significant. As for the Test of Sensory Functions in Infants, had significant difference between groups in total score (p=0.0113) and the sub item 1 (reactivity to tactile deep pressure) (p˂0.0001). Factors such as length of stay, maternal complications, complications in the NICU and brackets may be associates with this change. Among the most frequent maternal complication was hypertension, the brackets more used were oxygen and antibiotics, the most prevalent complications were hyaline membrane disease, and respiratory distress. A maternal and neonatal morbidity, in addition to prolonged hospitalization, may be associated with delayed motor development and the change in sensory processing, so it is essential to the assessment and referral to early intervention programs, justifying the need prevention strategies, as sensory an motor deficits may last throughout the years is most evident in the school year. Therefore, from the assessments, you can obtain information so that preventive measures can be implemented or, if necessary, therapies aimed at promoting development.